A noble metal-free candle soot derived carbon electrocatalyst for simultaneous H2 generation and wastewater treatment. (February 2023) - Pahra, Swapna; Sangabathula, Omkar; Sharma, Chandra S.; Devi, Pooja
Abstract: Electrocatalytic water splitting to produce green hydrogen is a promising approach for clean energy generation. However, the commercial aspect of this approach is limited due to catalysts cost and feedstock. Thus design of an inexpensive and noble metal-free (Pt, Rh, Ir etc.) catalyst is desirable. Moreover, wastewater as a feedstock for hydrogen generation is not explored to its full potential for green hydrogen generation, which otherwise is also a problem to be managed especially in developing countries. In the present work, we have investigated an inexpensive catalyst i.e. candle soot-derived carbon as an electrocatalyst for H2 generation from textile wastewater utilizing methylene blue as a model pollutant. The carbon catalyst is synthesized from the candle soot and is characterized for its structural and morphological properties. Carbon soot coated onto the nickel foam (CS@NF) proves as an efficient hydrogen evolution catalyst due to its excellent electrical conductivity and large active surface area. CS2.5 @NF (with the loading of 2.5 mg cm −2 ) shows an overpotential and Tafel slope of 117 mV and 43.85 mV/dec, respectively in an acidic medium containing textile pollutants. Under optimal condition, ∼62% degradation is achieved within ∼90 min, along with the stable hydrogen production of ∼0.158 mmol per hour. These preliminary findings demonstrate the potential usage of an inexpensive non-noble metal free catalyst for simultaneous wastewater treatment as well as hydrogen generation. Graphical abstract: Image 1 Highlights: A carbon based electrocatalyst, CS2.5 @NF, synthesized via simple flame combustion process. The in-expensive carbon catalyst shown for simultaneous textile water treatment and hydrogen generation. CS2.5 @NF acts as an excellent electro catalyst for HER in textile wastewater with an over potential of 117 mV Vs. RHE. The designed electro catalyst exhibits degradation efficiency of ∼62% and hydrogen evolution rate of 0.158 mmol/h.